A preliminary report on newly discovered fluvial vessels from Kostolac, Serbia - Jevtović, Ljubomir; Stojić, Goran; Danković, Ilija; Divić, Anton (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The paper presents the results of a preliminary study of a group of four fluvial vessels recently discovered in the vicinity of Kostolac (NE Serbia), dated between the Late Iron Age and the Late Medieval Period. The remains of four vessels were discovered in March 2020 during regular mining activity at the “Drmno” strip coal mine, at four kilometers’ distance from the contemporary course of the Danube. Four different vessels were identified among the wooden remains, well preserved under six meters of clay-like sediment: two dugouts, a single plank belonging to a flat-bottomed vessel, and a well-preserved flat-bottomed planked barge. While focusing on the architectural characteristics and nautical capabilities of the discovered vessels, this paper will also present preliminary conclusions on the context of their discovery concerning the archaeological topography of the region.